INVESTIGATING THE IMPACT OF IFRS 16 ADOPTION IN SERBIAN HOTEL INDUSTRY - Kljajić, Maja; Mizdraković, Vule (The European Journal of Applied Economics, 2024)
The effects of the implementation of IFRS 16 in the hotel industry, as one of the industries with the highest amounts of leased assets, is the primary focus of this paper. The International Accounting Standards Board addopted International Financial Reporting Standard 16 - Leases in January 2016, replacing International Accounting Standard 17 – Leases, for reporting periods starting on or after 1st January 2019. The updated regulations introduce different accounting models for lessees and lessors. The influence of IFRS 16 on a reporting entity is contingent on the quantity of existing operating lease agreements and differs across various industries. The research sample includes financial reports of 64 hotels per reporting period (2020-21), totaling 128 observation units. Data analysis included the application of statistical tests such as Kolmogorov-Smirnov test, Shapiro-Wilk test, and Wilcoxon signed-rank test. The research results indicate that aside other events, adoption of IFRS 16 had an impact on the financial performance of observed hotels and their key financial statements items.